Penyusunan Laporan Keuangan Sederhana Bagi Pelaku UMKM Kota Tangerang Selatan - Agus Setyo Pranowo; Ida Zuniarti; Lia Mazia; Windi Windi; Nono Arief Rachman; Isbat Isbat; Ismet Alimin; Universitas Pakuan; Nanang Qosim Yusuf; Henry Lasut; Yuhelmis Sienifa (Institut Teknologi dan Bisnis Semarang, 2024)
Community service activities are carried out to increase the competitiveness of South Tangerang City MSMEs in the era of society 5.0. In order to achieve this goal, there are various training activities in this community service, one of which is training in preparing simple financial reports, including introducing account names in accounting, recording transactions in basic accounting equations and preparing financial reports. Training in preparing simple financial reports as a strategic step to improve the skills of Micro, Small and Medium Enterprises (MSMEs) in South Tangerang City in managing financial transactions. The main aim of this activity is to provide practical understanding and support to MSMEs in preparing simple but informative financial reports. The service method is carried out by providing training and direct assistance to MSME actors in South Tangerang City. The material presented includes the basics of accounting, recording transactions in basic accounting equations, as well as preparing financial reports, and interpreting financial information that is relevant for the needs of small-scale businesses. Training activities showed the results of increasing knowledge about preparing reports for MSME actors in South Tangerang City by 47%. The implications of this service activity can be used as a basis for developing similar programs to support the development of MSMEs and encourage economic growth at the local level.